2014
DOI: 10.1073/pnas.1315275111
|View full text |Cite
|
Sign up to set email alerts
|

Categorical encoding of color in the brain

Abstract: The areas of the brain that encode color categorically have not yet been reliably identified. Here, we used functional MRI adaptation to identify neuronal populations that represent color categories irrespective of metric differences in color. Two colors were successively presented within a block of trials. The two colors were either from the same or different categories (e.g., "blue 1 and blue 2" or "blue 1 and green 1"), and the size of the hue difference was varied. Participants performed a target detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
90
4
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(109 citation statements)
references
References 45 publications
12
90
4
3
Order By: Relevance
“…Color processing depends upon an extensive network of brain regions that process retinal signals (40), culminating in the highest levels of processing, in frontal cortex (41). The present report leverages color language as perhaps the best readout of this machinery as it pertains to behavior to uncover the forces behind the most fundamental color categorization, warm versus cool.…”
Section: Discussionmentioning
confidence: 90%
“…Color processing depends upon an extensive network of brain regions that process retinal signals (40), culminating in the highest levels of processing, in frontal cortex (41). The present report leverages color language as perhaps the best readout of this machinery as it pertains to behavior to uncover the forces behind the most fundamental color categorization, warm versus cool.…”
Section: Discussionmentioning
confidence: 90%
“…Previous functional neuroimaging studies have associated area V4, located in the fusiform gyrus, as an important site for color perception in the adult human brain (33)(34)(35). A recent fMRI study reported that the categorical clustering of neural representation for color-naming was found in the ventral visual areas V4v and VO1 (20), whereas these areas seem to change their responses flexibly under different tasks (19), probably according to the top-down signal from higher order areas that define categories (31). An electrophysiological study in macaque monkeys' inferior temporal cortex (18) showed the presence of neurons with selectivity for color categories, which was highly similar to the categories measured by psychophysics in humans (32).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence that is consistent with nonverbal categorization taking place within perception includes neural evidence of early categorical encoding in the brain (Stoughton & Conway, 2008;Bird et al, 2014), categorical color constancy in perception of real-world scenes (Olkkonen et al, 2010), and categorical effects on visual search for colored targets (Daoutis et al, 2006). The reported results contribute to this body of evidence by demonstrating that categorization influences matching performance even with an in-view stimulus.…”
Section: Color Terms and Categories; Verbal Versus Visual Memorymentioning
confidence: 96%